A study of the effect of change on the perceived levels of power, conflict and satisfaction in a channel of distribution. - Kindelsperger, Bren Willard. (My University, 1982)
This change was regarded by the manufacturer as being significant to its overall marketing and sales effort and it was presumed to be received favorably by the distributors. The results of this study indicated that there was in fact no perceived change in the levels of power, conflict, and satisfaction. In fact there were no changes recorded in any of the response levels to the questionnaire elements.

Hypotheses were developed on how these relationships should change due to the initiation of the policy change of the manufacturer.

This study was concerned with the effect made on the levels of perceived power, conflict, and satisfaction made by a change to a significant element of the business relationship. The study also attempted to analyze the relationship between the three variables during this change in the functioning of the channel of distribution. The element of intensity was also introduced to analyze the relationship intensity will have on the variables of power, satisfaction, and conflict.

An established channel of distribution was selected where the manufacturer had decided to impose a change to a significant item of the business relationship. A field study was conducted to accumulate data concerning the perceptions of the distributors on major elements of the business relationship in the areas of power, control, and satisfaction. A prepared questionnaire was used as a research instrument to accumulate this data. The change was initiated by the manufacturer and the same research instrument was applied again to accumulate the responses by the distributors to this change.

After research into the possible causes of these results, possible causes for the condition were discussed. The major factor, determined through investigations with the manufacturer, was that the communication of the change was not received and therefore not known by the major distributors in the organization. The communications problem caused substantial repercussions at the manufacturers level, as well as developing additional implications for future research. The major implication for future research would be in the area of the communications process and its effect on the variables of power, conflict, and satisfaction.

The channel of distribution contains the properties of specialization and functional differentiation which lead to interdependency among the channel members. Because these interdependencies will be of varying degrees, it gives rise to power relations between the organizations. In addition, the dependency relationship brings about the beginnings of a conflict situation. The amount of satisfaction felt by the participants in a channel of distribution may have a significant effect on the operation of the channel as well as an interaction with the variables power and control.
Keywords: Business Administration, Marketing.